Simulation of pure and defective wurtzite-type ZnO - Maldonado, F. (2009)
Changes in the structural and electronic properties of zinc oxide (ZnO) due to the O vacancy and F-centre were studied using a semi-empirical quantum-chemical approach based on Hartree-Fock theory. A periodic supercell of 128 atoms was exploited throughout the study. The semi-empirical parameters for the Zn atom are obtained by reproducing the main properties of the ZnO crystal as well as the first three ionization potentials of the Zn atom. The perturbation imposed by the defect leads to atomic relaxation, which is computed and discussed in detail. It is found that electron density redistribution in the vicinity of defects plays an important role in the determination of atomic movements. The introduction of an oxygen vacancy generates a local one-electron energy level placed below the conduction band while the presence of an F-centre produces a local energy level just above the upper valence band of the material. The deep situation of the local energy level corresponding to the F-centre implies that the F-centre cannot serve as a source of unintentional n-type electrical conductivity in ZnO. Changes in the chemical bonding are observed, showing that it becomes slightly more covalent because of oxygen-vacancy-type defects. © 2009 The Royal Swedish Academy of Sciences.